2017
DOI: 10.1002/sim.7273
|View full text |Cite
|
Sign up to set email alerts
|

Firth's logistic regression with rare events: accurate effect estimates and predictions?

Abstract: Firth's logistic regression has become a standard approach for the analysis of binary outcomes with small samples. Whereas it reduces the bias in maximum likelihood estimates of coefficients, bias towards one-half is introduced in the predicted probabilities. The stronger the imbalance of the outcome, the more severe is the bias in the predicted probabilities. We propose two simple modifications of Firth's logistic regression resulting in unbiased predicted probabilities. The first corrects the predicted proba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
243
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(251 citation statements)
references
References 16 publications
7
243
0
1
Order By: Relevance
“…As overall performance is composed of discrimination and calibration, the improvement in calibration improves the overall performance. Our results indeed showed that the overall performance was slightly better for penalized than for unpenalized MLR, which is in agreement with earlier simulation studies on binary logistic regression …”
Section: Discussionsupporting
confidence: 92%
“…As overall performance is composed of discrimination and calibration, the improvement in calibration improves the overall performance. Our results indeed showed that the overall performance was slightly better for penalized than for unpenalized MLR, which is in agreement with earlier simulation studies on binary logistic regression …”
Section: Discussionsupporting
confidence: 92%
“…Puhr et al . () proposed the FLAC approach to overcome the bias problem in average predicted probabilities of the Firth estimator. The method involves the following steps.…”
Section: Models and Predictive Accuracy Measuresmentioning
confidence: 99%
“…This is in line with the submission in Puhr et al . (), who opined that the Firth method introduces bias in predicted probabilities. Ridge in contrast does not perform well at EPV=2 when the AUROC is used to evaluate discrimination.…”
Section: Simulation Based On the Taiwan Credit Card Data Setmentioning
confidence: 99%
See 2 more Smart Citations